Pengembangan Kurikulum Muatan Lokal Pendidikan Al-Quran (Studi Multikasus di MI Darul Azhar Simpang Empat dan SDN 1 Tungkalan Pangeran Simpang Empat Kabupaten Tanah Bumbu Kalimantan Selatan ) - Mahmudah, Mahmudah (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2016)
Local contain of Al Quran education is learning which give opportunity students to learn, applicative and do all Al Quran doctrines. The focus that is process and knowing about reading, writing, and Al Quran understanding useful for life. In fact, the local contain Al Quran education at year 2009 that first published Province Regulation. By published Province Regulation South Kalimantan No. 3 year 2009 about Al Quran education in South Kalimantan The aims of Al Quran education is every students can be read, write Al Quran character well, understand and use full all doctrine Al Quran for life. Development curriculum in this study are action of perfecting based element Al Quran education has use by Province Government. And every school program development to increase student ability with learn school activities to get vision an purpose of  school. This research aims to describe curriculum development Al Quran education in Islamic Elementary Darul Azhar and State Elementary School 1 Tungkalan Pangeran Simpang Empat South Kalimantan. This research use a qualitative approach with planning multi case study. Methods of data collection through interviews, observation, and documentation. And the research informer is head school, vice head curriculum, Al Quran education teacher supervisor. All data be analysed in this case  and cross analysis. While data validity use triangulation source and method. The results from this research is: (1) curriculum plan envelop background, source idea, purpose, principle, content analysis, evaluation. (2) curriculum realization is envelop intra curricular, extracurricular  and for example. (3) curriculum evaluation is envelop programme, realization, and assessor. (4) curriculum development model of local contain Al Quran education have characteristic top an down.